Dampak Perubahan Iklim terhadap Kesehatan Masyarakat Pesisir dan Strategi Adaptasinya - Muhammad Ardhonillah Ramadhan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Climate change is a change in climate conditions caused by human activities, either directly or indirectly, resulting in changes in the global atmospheric composition and changes in natural climate variability over an extended period. Coastal areas are among the most vulnerable regions to the impacts of climate change, including on public health aspects, such as an increased risk of infectious disease due to tidal flooding, abrasion, and extreme weather, as well as disruption to health service access and fishermen's livelihoods. This study aims to examine the impact of climate change on coastal community health and the adaptation strategies that have been and can be implemented. This research uses a literature review method, with data obtained through a search of articles on Google Scholar, official websites, and relevant institutions in accordance with the research theme and title. The results show that structural adaptation strategies in coastal areas such as Ulee Lheue and Gampong Lampulo are carried out through the construction of sea walls to withstand high waves and prevent seawater intrusion, improvement of drainage channels and canal systems to facilitate water flow and reduce inundation due to tidal flooding or heavy rain, as well as the construction of breakwaters to protect the coast from abrasion. In addition, non-structural adaptation through policy and education, as well as community-based adaptation such as mangrove replanting, also play an important role in strengthening the resilience of coastal communities. Although this physical development is effective in the short term, the main challenge faced is the limited local government budget for long-term maintenance and weak cross-sectoral coordination.